Dynamics of morbidity indicators of neurotic, stress-related and somatoform disorders in the rural population of Ukraine - Zinchenko, Olena M. (Psychiatry, Neurology and Medical Psychology, 2020)
In order to study the dynamics of indicators of the incidence of neurotic, stress-related and somatoform disorders in the rural population of Ukraine, an analysis of statistical data of reporting forms No. 10 “Report on diseases of persons with mental and behavioral disorders” reflecting the objectively taken into account the incidence of neurotic, stress-related and somatoform disorders for 2000 - 2017 years. The analysis revealed the main features of neurotic morbidity associated with stress and somatoform disorders in the rural population of Ukraine for the period from 2000 to 2017. Thus, the primary incidence rate of neurotic, stress-related and somatoform disorders in the rural population of Ukraine for the period from 2000 to 2017 decreased by 9.11% (from 45.0 per 100 thousand of the rural population in 2000 to 40, 9 per 100 thousand urban population in 2017). The overall incidence rate of neurotic, stress-related and somatoform disorders in the rural population of Ukraine tended to gradually increase, from 259.0 in 2000 to 313.3 per 100 thousand rural population in 2017. A significant proportion of neurotic, stress-related and somatoform disorders in the structure of the incidence of non-psychotic mental disorders and the identified regional features of the dynamics of the primary and general morbidity of neurotic, stress-related and somatoform disorders in the rural population of Ukraine should be taken into account when developing organizational measures to optimize the system of assistance and prevention rural mental health disorders.